2013
DOI: 10.1038/jid.2012.403
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Recurrence 5 Years after Treatment of Cutaneous Basal Cell Carcinoma and Squamous Cell Carcinoma

Abstract: For most cutaneous basal cell and squamous cell carcinomas (nonmelanoma skin cancers [NMSC]) data are insufficient to permit evidence-based choices among treatments. To compare tumor recurrence after treatments, we conducted a prospective cohort study of consecutive patients with primary NMSC treated with the most common treatments in two practices in 1999–2000. Recurrence was determined from medical records by observers blinded to treatment type. 24.3% of tumors (N=361) were treated with destruction with elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
1
20

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 26 publications
11
137
1
20
Order By: Relevance
“…Overlapping CIs for average effect estimates for the different treatments suggest that apparent differences between treatments may not be significant. This is in agreement with finding of Chren et al 659 who conducted a large prospective cohort study of all primary NMSCs and reported no significant difference in hazard of recurrence between surgically excised tumours and those treated with MMS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Overlapping CIs for average effect estimates for the different treatments suggest that apparent differences between treatments may not be significant. This is in agreement with finding of Chren et al 659 who conducted a large prospective cohort study of all primary NMSCs and reported no significant difference in hazard of recurrence between surgically excised tumours and those treated with MMS.…”
Section: Discussionsupporting
confidence: 93%
“…It is also possible that SCCs that were treated by destructive modalities such as cryotherapy or 659 This was supported by our recent systematic review and pooled analysis of treatments for SCC in which there was significant overlap of CIs between different treatment modalities. 536 Although only a small percentage of SCCs recur, it is important to identify those that are at greatest risk of recurring at an early stage.…”
Section: Summary Of Number Of Patients Potentially Eligible For the Pmentioning
confidence: 80%
See 1 more Smart Citation
“…Standart eksizyon 5 yıllık rekürrens oranlarının %2-10 arasında değiştiği bütün primer BHK olgularda etkili tedavi seçeneğidir [20][21][22] . Genel kabul gören güvenli cerrahi sınır 3-5 mm.…”
Section: Bhk Tedavi Seçenekleri Ve Güncel Yaklaşımlarunclassified
“…Mohs surgery is a proven and well‐known procedure for skin cancer treatment, with five‐year cure rate of 97%‐99% (6) . However, Mohs surgery requires the preparation and examination of frozen pathology, representing a relatively labor‐intensive, time‐consuming, and expensive process.…”
Section: Introductionmentioning
confidence: 99%